STUDI FENOMENOLOGI : KEBUTUHAN PENDIDIKAN KESEHATAN PADA PASIEN FRAKTUR EKSTREMITAS ATAS - Iswatun Iswa Qasanah; Eko Winarto; Yunani Yunani (Universitas Muhammadiyah Kudus, 2023)
AbstractBroken bones or fractures are sudden situations where the client or family has no preparation to deal with the conditions that are happening. Fractures will have an impact on both the client and the family, for this reason the problems in cases of extremity fractures need to be studied further, so that they can provide an explanation regarding prevention or protective measures for extremity fracture clients and their families. In fact, there is no instrument that can identify the needs and learning characteristics of clients with upper extremity fractures. Existing instruments are in the form of assessment forms and general patient and family education plans that are used for all hospitalized patients with various cases. This study aims to explore the need for health education in upper extremity fracture patients. This study uses a qualitative research design with a phenomenological approach. Data collection was obtained by means of in-depth interviews. Participants were 5 patients with upper extremity fractures. Content validity test by 2 experts and 3 hospital practitioners. The analysis was carried out using the Colaizzi method. From the research results identified six main themes: (1) Perceived obstacles, (2) Perceived benefits of action, (3) Confidence, (4) Situational influence, (5) Interpersonal influence, (6) Commitment to plan an action. Results The content validity of each of the 28 items resulted in a Vaiken index value 0.80. This shows that all of the assessment instruments developed in this study in terms of their contents can measure what should be measured. Therefore, all of the instruments can be said to be feasible to use or be tested on respondents in order to obtain empirical evidence of the quality of the instrument.Keywords: Extremity Fracture, Needs, Health Education